Thirty-gauge needle-guided purse-string suture pupilloplasty: a new technique - Chun-Ming Chen; Hong Zhong; Yan Shao; Cheng-Yao Qin; Ze-Hao Liu; Wen-Xiu Sun; Min Li (International Journal of Ophthalmology)
AIM: To observe the clinical outcomes of 30-gauge (G) needle-guided 10-0 prolene suture purse-string pupilloplasty for atonic pupil management. METHODS: Eight patients with atonic pupils who underwent suture purse-string pupilloplasty were retrospectively analyzed. Preoperative data and at least 6mo of postoperative data were collected from all the patients. RESULTS: The corrected distance visual acuity (CDVA) before and after surgery was 0.58±0.22 and 0.20±0.10 logMAR, respectively (P=0.002). The pre- and postoperative pupil size was 7.38±0.88 and 3.09±0.71 mm (P=0.000), respectively. The corneal endothelial cell count was 2841±176/mm2 before and 2692±143/mm2 after surgery (P=0.000). No intraoperative or postoperative complications were reported. During the follow-up period of at least 6mo, all treated pupils were centered and generally or nearly round. Furthermore, the patients did not exhibit photophobia, glare, or diplopia. CONCLUSION: This technique is a simple and effective method for pupil reduction.